Dietary myo‐inositol requirements of juvenile hybrid sturgeon (Acipenser baerii ♀ × A. schrenckii ♂). (13th January 2020) - Li, Yan; Wu, Jinping; Chen, Xihua; Chu, Zhipeng; Jin, Jiali; Tang, Dan
Abstract: This study was conducted to determine the optimal dietary myo‐inositol (MI) requirement of juvenile hybrid sturgeon ( Acipenser baerii ♀ × A. schrenckii ♂). Fish with an initial average body weight of 28.28 ± 0.41 g were randomly divided into six groups with three repetitions in each group and fed the experimental diets with different graded MI concentrations (70.2, 130.0, 270.2, 443.0, 1, 096.6 and 1997.3 mg/kg) three times per day for 12 weeks. The results showed that with the increase in dietary MI level from 70.2 mg/kg to 443.0 mg/kg, weight gain (WG) was increased significantly ( p < .05); however, when the MI level was further increased, there was no significant difference in weight gain rate (WG) over time ( p > .05). Specific growth rate (SGR) showed a similar trend. The feed conversion ratio (FCR), survival rate (SR), hepatosomatic index (HSI), viscerasomatic index (VSI) and condition factor (CF) were not affected by dietary MI supplementation ( p > .05). Dietary MI did not affect whole‐body and muscle crude protein and ash content ( p > .05), while dietary MI significantly affected the muscle and whole‐body crude lipid and moisture content ( p < .05). Moreover, serum triglyceride (TG), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels were decreased by increasing dietary MI levels. Total antioxidant capacity (T‐AOC), malonic dialdehyde (MDA) and superoxide dismutase (SOD) activities in the liver were also affected by the dietary MI ( p < .05). In summary, this study indicated that the optimal dietary MI requirement for juvenile hybrid sturgeon ( Acipenser baerii ♀ × A. schrenckii ♂ ) was 335.84 mg/kg and 590.65 mg/kg based on the maximum WG and liver MI accumulation indices respectively.